Tuning Pt II ‐Based Donor–Acceptor Systems through Ligand Design: Effects on Frontier Orbitals, Redox Potentials, UV/Vis/NIR Absorptions, Electrochromism, and Photocatalysis - Sobottka, Sebastian; Nößler, Maite; Ostericher, Andrew L.; Hermann, Gunter; Subat, Noah Z.; Beerhues, Julia; Behr‐van der Meer, Margarethe; Suntrup, Lisa; Albold, Uta; Hohloch, Stephan; Tremblay, Jean Christophe; Sarkar, Biprajit (Chemistry : a European journal, 2020)
Asymmetric platinum donor–acceptor complexes [(pimp)Pt(Q 2− )] are presented in this work, in which pimp=[(2,4,6‐trimethylphenylimino)methyl]pyridine and Q 2− =catecholate‐type donor ligands. The properties of the complexes are evaluated as a function of the donor ligands, and correlations are drawn among electrochemical, optical, and theoretical data. Special focus has been put on the spectroelectrochemical investigation of the complexes featuring sulfonyl‐substituted phenylendiamide ligands, which show redox‐induced linkage isomerism upon oxidation. Time‐dependent density functional theory (TD‐DFT) as well as electron flux density analysis have been employed to rationalize the optical spectra of the complexes and their reactivity. Compound 1 ([(pimp)Pt(Q 2− )] with Q 2− =3,5‐di‐ tert ‐butylcatecholate) was shown to be an efficient photosensitizer for molecular oxygen and was subsequently employed in photochemical cross‐dehydrogenative coupling (CDC) reactions. The results thus display new avenues for donor–acceptor systems, including their role as photocatalysts for organic transformations, and the possibility to introduce redox‐induced linkage isomerism in these compounds through the use of sulfonamide substituents on the donor ligands.